INTER STAKEHOLDERS PARTNERSHIP IN THE DEVELOPMENT OF HANDYCRAFT SMALL INDUSTRY AS THE BASIS OF LOCAL ECONOMIC DEVELOPMENT IN GUNUNGKIDUL REGENCY - M. HASAN (NIM 25407081); Pembimbing: Dr. Ir. Dewi Sawitri, M.T., RISNA
In Local Economic Development, the existence of small industry has an important it generally grows as result of local entrepreneurship and emphasizes more on the utilization of local labor and materials so that the existence of this small industry has potency as the driving force of the growth of local economic activities in the region. One of the small industry development strategis to support Local Economic Developmnet through business partnership as an effort to grow locality by combining, organizing, and transforming all existing local potency, especially marketing and funding in order to create development synergy. This study was conducted in three handycraft small industries centers in Gunungkidul Regency, i.e. the center of mask and wooden batik handycraft small industry in Bobung, Patuk, the center of stone ornamnet handycraft small industry in Semanu, and the center of bamboo handycraft small industry in Semanu. The impact of existence of these industries has not contributed significantly to regional that the craftsmen are depended on the buyers/exporters. The purpose of this study is look at the pattern of stakeholders partnership in an effort to develop handycraft small industry in Gunungkidul regency. The partnership that is going to be identified is the partnership among the handycraft small industries, partnership between handycraft small industry and buyers/exporters/BUMN/Associated, partnership between handycraft small industry and universities, and partnership between handycraft small industry and government. The result shows that the pattern of partnership that exists are mostly in the form of sub contract of ’semi finished goods’, general trade between buyers and producers, training and education, facilitating the promotion of small industry product. Factors influencing partnership are limited demand, lack of open communication and trust, lack of willingness/interest of the traders/exporters, business motivation, willingness, business feasibility, and program motivation. The study concludes that the existing partnership has not occurred entirely in three studied handycraft small industries. The center of handycraft small industry that has implemented some of partnership pattern is the center in Bobung, so that this center is more developed that the others. The partnership pattern that should occur among the handycraft small industries as the main stakeholders is partnership in technology utilization in order to pruduce designs with high selling vallue. The partnership pattern in these three centers has not been able to be called a partnership that should occur in the development of handycraft small industry because they are not at the same position and has not been based on the principle of needing each other, strengthening each other, and benefiting each other. Based on the result of the study, some directions for the improvement of the partnership are proposed, i.e.: 1) improvement of the quality of the handycraft produsct through technology innovation development; 2) strengthening of the existing cooperative agency; 3) increasing government support in the development of handycraft small industry through empowerment program in the development of production technology, management, capital, and marketing; 4) increasing the role of government in mediating partnership between small industry and traders/exporters; 5) increasing the role of gevernment in mediating partnership between small industry and state-owned enterprise through socialization; 6) increasing the role of government in mediating partnership between handycraft small industry and universities; and 7) developing industrial cluster as the manifestation of business correlation among the small industries at the center.